Solidarność jako zasada życia społecznego w nauczaniu Jana Pawła II - Kowalczyk, ks. Stanisław (Annales. Etyka w Życiu Gospodarczym, 2011)
The paper has three parts. The first part concerns the solidarity principle’s genesis. Its philosophical base is the personalistic anthropology, which speaks about prosocial nature of man and its active participation in the social life. The biblical-theological base of solidarity are: personal dignity of man comme God’s image, person and learning of Christ, community of the Church. The second part of paper discusses elements ontological-anthropological and biblical-ethical which are necessary in the realisation of solidarity’s principle. They are following: pluralism of equal persons and societies, its dialogue, co-production of common good by honest work, integral development economic and intelectual-cultural, equality, social justice and love, peace and reciprocal settlement. The thirt part of paper speaks about three circles of application of solidarity’s principle; namely: solidarity professional-working – defend of rihts of workers, solidarity general-social of nation and state – protection of economic and political human rihts, solidarity international of humanity – trend towards peace and prosperity.